Metal semiconductor core-shell nanostructures for energy and environmental applications - Gupta, Raju Kumar 1982-; Misra, Mrinmoy (Elsevier, 2017)
Metal Semiconductor Core-Shell Nanostructures for Energy and Environmental Applications provides a concise, scholarly overview of current research into the characterization of metal semiconductor core-shell nanostructures; the book shows how their properties can be best used in energy and environmental applications, particularly for solar cell and catalysis application. Coverage is also given to the effect of metal nanoparticle for charge generation or charge separation. The book is a valuable resource for academic researchers working in the areas of nanotechnology, sustainable energy and chemical engineering, and is also of great use to engineers working in photovoltaic and pollution industries.--Provided by publisher.